"Where's home, Ulysses?" Judith Wright in Europe 1937. (June 2017) - Kennedy, Sarah
When Judith Wright travelled to Europe in the "loaded spring" of February 1937, the 22-year-old poet found herself witness to "a break in the consciousness of Europe". This article argues that Wright's experience of being an outsider in Europe at this crucial historical moment had profound implications for her poetics, in the form of a compound and productive series of displacements. Her peripatetic encounters with European cultures-in-crisis caused Wright to despair of Europe as a source of political and creative renewal, and exposed fault lines in her own cultural orientation. Sundered from her Anglophile cultural inheritance, and able to reflect on home with the distance and imaginative ambivalence of an outsider, Wright invoked Ulysses — that archetypal poetic wanderer — whose experience of archipelagic journeying came to express for her the contingencies and hauntedness of Australia's palimpsestic identity. This essay positions the shifting perspectives and excursive patterns of Wright's developing poetics in relation to concepts of outsideness and embodiment, drawing on the work of Mikhail Bakhtin and phenomenological philosophies of mind.